Implementasi Honeypot Menggunakan Dionaea Dan Kippo Sebagai Penunjang Keamanan Jaringan Komunikasi Komputer - Adi Widiatmoko Wastumirad; Moh Irzam Darmawan (Jurnal Teknologi, 2021)
Today, the internet has become the most used tool for delivering information. Through the internet, people can search for information by freely accessing a web page. This freedom of access often raises security issues in the website provider's internal network. These security issues can be in the form of misuse of information, threats, and other attacks on the provider's internal network. Based on these conditions, a technique is needed to protect important data on the website owner's server from various attacks. In this research, a Honeypot security system has been implemented using Dionaea and Kippo in the Demilitarized Zone to increase the security of a network. The methodology of this research is Waterfall Model for software engineering. The system that has been built is able to detect, take action, record attack logs and display them in the form of a website in real time.